Surface modification of titanium(IV) oxide sol-gel powders by sulfur - Vakhula, Yaroslav; Besaha, Khrystyna; Lutsyuk, Iryna (Publishing House of Lviv Polytechnic National University, 2012)
The synthesis of titanium(IV) oxide nanopowders modified by sulfur with the help of sol-gel method has been described. The structure of surface layers has been investigated using X-ray diffraction analysis, a scanning electron microscopy, IR-spectroscopy and X-ray photoelectron spectroscopy. The possible mechanism of powders surface modification by sulfur has been shown, as well as the dependence of specific surface on sulfur content. Золь-гель методом синтезовано нано- порошки титану(IV) оксиду модифіковані сіркою. Структуру поверхневих шарів досліджено за допомогою рентгено-дифракційного аналізу, скануючої електронної мікроскопії, ІЧ-спектроскопії та рентгенівської фотоелектронної спектроскопії. Показаний можливий механізм модифікації поверхні, а також встановлено залежність питомої поверхні від вмісту сірки.
Поверхневе модифікування сіркою золь-гель порошків титану(IV) оксиду
Keywords: sol-gel powders; S-TiO2; surface modification; золь-гель порошки; S-TiO2; модифікування поверхні